Keefektifan Model Perkuliahan Investigasi Kelompok yang Bermuatan Nilai-Nilai Konservasi untuk Meningkatkan Keterampilan Menulis dan Pengembangan Karakter Mahasiswa FBS UNNES - Mimi Mulyani; Rina Supriananingsih (Universitas Tidar, 2019)
The purpose of this study was to determine the effectiveness of the group investigation learning model that contained conservation values in writing learning and character development of UNNES FBS students. This learning model was chosen because it is one of the social interaction learning models that require students to have the ability to interact with their conservation environment and work together in groups in synergy. The ultimate goal of this experimental research is to find the effectiveness of the development products produced in previous studies, namely the group investigation learning model containing conservation values to improve writing skills and instill/ develop character values of FBS UNNES students. The approach applied in this study is quasi-experiment with pretest-posttest design, non-equivalent control group design. Determination of research samples using purposive samples. Respondents of this study were students of Indonesian Language and Literature Education Study Program FBS UNNES in semester one. Data collection uses to test and non-test instruments — analysis of research data using validity test, reliability test, homogeneity test, and t-test.